ANTI-ULCEROGENIC EFFICACY AND MECHANISMS OF EDIBLE AND NATURAL INGREDIENTS IN NSAID-INDUCED ANIMAL MODELS - Bi, Weiping; Hu, Lizhi; Man, Mao-Qiang (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are a class of the most commonly used medicines and proven to be effective for certain disorders. Some people use NSAIDs on daily basis for preventive purpose. But a variety of severe side effects can be induced by NSAIDs. Studies have shown that edible natural ingredients exhibit preventive benefit of gastric ulcer. This paper reviews the efficacy and safety of edible natural ingredients in preventing the development of gastric ulcer induced by NSAIDs in animal models.Methods: A systematic literature search was conducted on PubMed, using the terms “herbal medicines” and “gastric ulcer”, “herbal medicines” and “peptic ulcer”, “food” and “peptic ulcer”, “food” and “gastric ulcer”, “natural ingredient” and “peptic ulcer”, “natural ingredient” and “gastric ulcer”, “alternative medicine” and “peptic ulcer”, “alternative medicine” and “gastric ulcer”, “complementary medicine” and “peptic ulcer”, “complementary medicine” and “gastric ulcer” in papers published in English between January 1, 1960 and January 31, 2016, resulting in a total of 6146 articles containing these terms. After exclusion of studies not related prevention, not in NSAID model or using non-edible natural ingredients, 54 articles were included in this review.Results: Numerous studies have demonstrated that edible natural ingredients exhibit antiulcerogenic benefit in NSAID-induced animal models. The mechanisms by which edible, ingredient-induced anti-ulcerogenic effects include stimulation of mucous cell proliferation, antioxidation, inhibition of gastric acid secretion, as well as inhibition of H (+), K (+)- ATPase activities. Utilization of edible, natural ingredients could be a safe, valuable alternative to prevent the development of NSAID-induced gastric ulcer, particularly for the subjects who are long-term users of NSAIDs.